O ente coletivo e o princípio nemo tenetur se ipsum accusare - Pereira, Estrela Vanessa Lucas (2019)
This dissertation deals with nemo tenetur se ipsum accusare principle and its importance to the legal person when accused. The first point refers to nemo tenetur principle and its corollaries. In a second point, we are going to investigate the contours of its application to the legal person. The application of the right to silence to legal person involves several questions that hasn't a procedurally answers, but which raise complexities regarding the extent of this right within the legal person. The same happens to the right against self-incrimination, which must be combined with the self-incrimination of the legal person itself and with the self-incrimination of the other organ owners and members of the legal person. Finally, this dissertation also deals with the exceptions at nemo tenetur principle, embodied in the duties of collaboration, especially the extra-procedural ones and those who appears outside the procedural collaboration that is required to the defendant in criminal proceedings. It is therefore necessary to examine the exercise of the right to silence and the right to self-incrimination by the concerned, which is the subject of collaborative duties in the supervision of economic activities. The purpose of this dissertation is to demarcate the complexities associated with the exercise of procedural prorogations by the legal person, taking into account its organic and organizational structure. We also aim to investigate the maintenance of the duties of collaboration when there is a suspicion against the concerned, as well as the contours of the elements brought by the concerned, which can be used for the duties of collaboration in a subsequent sanctioning process, especially a criminal one.